Use of learning analytics in the flipped classroom: a systematic review - Alexandro Escudero-Nahón; Emma Patricia Mercado López (Universidad de Guadalajara, 2019)
Learning analytics is a method of measuring, collecting, analyzing and reporting large volumes of data on apprentices in their learning contexts. The purpose is to predict the potential educational problems that could arise anticipate effective solutions and, in this way, improve academic performance. Learning analytics opens new opportunities to adequately evaluate new didactic strategies that incorporate digital technology, such as the flipped classroom. A systematic review was performed to identify the state of knowledge about the Learning Analytics within the lipped classroom. The results suggest: a) the use of Learning analytics within the flipped classroom in the last year has increased; b) its use has been addressed, indeed, to identify the learning behaviors of the students and to evaluate the academic achievement; c) in the cases in which the learning analytics was correctly applied, an improvement was obtained in academic achievement, self-regulated learning, motivation for study, collaboration and participation among students. However, the use of learning analytics has not yet been extended as much as other traditional methods that have also evaluated academic achievement within the flipped classroom.